Respuesta :
x2 = x2 + 2x + 9 Now subtract x2 from both sides and you have
x2- x2 = x2 - x2 + 2x + 9 or 0 = 2x + 9 now subtract 9 from both sides so you can solve for x.
0 -9 = 2x -9...and you have -9 = 2x
Now solve for x by dividing both sides by 2 and you arrive at x = -4.5
x2- x2 = x2 - x2 + 2x + 9 or 0 = 2x + 9 now subtract 9 from both sides so you can solve for x.
0 -9 = 2x -9...and you have -9 = 2x
Now solve for x by dividing both sides by 2 and you arrive at x = -4.5
Answer:
x = - 4.5
Step-by-step explanation:
The given expression is x² = x² + 2x + 9
we have solve the equation.
In this equation we will transfer like terms in one side of the equation.
x² - x² = 2x + 9
2x + 9 = 0
Now we subtract 9 from each side of the equation.
2x + 9 - 9 = 0 - 9
2x = -9
Now we will divide by 2 on each side of the equation.
2x/2 = -9/2
x = -4.5